Empowerment of Communities Affected by Covid 19 Through Strengthening Management and Technology Aspects Marketing For SMEs - Ismet Susila; Weny Almoravid Dungga; Tineke Wolok; Sartika Dewi Usman (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
In Gorontalo Province, the COVID-19 pandemic has lasted for approximately one year. One of the affected areas is North Gorontalo Regency which is directly adjacent to Central Sulawesi Province and North Sulawesi Province. This area has a lot of marine wealth potential that has not been managed. One of them is the great potential of seaweed. In this area the level of seaweed production reaches ± 28,866 tons/year. Of this amount, only about 20% is used by local processing industries as food processing materials, while 80% is sent to processing factories in the cities of Manado, Makassar and Surabaya . This happens because of two things: 1) the application of functions and elements of management has not been maximized, 2) there is no concept of center development and group development. Therefore, assistance from related parties, including universities in the transfer of management technology and standardization of product processing diversification for the development of SME centers is highly expected. In general, the purpose of the activity this is to reduce the negative impact of the spread of covid 19, especially for the community of seaweed SMEs in Katialada village. The method used is technical guidance on the management of processed seaweed diversification and assistance in the application of management functions and elements, industrialization and product standardization as well as the development of processed products to local and national markets. The results of the service are expected to increase economic added value for coastal community groups directly affected by COVID-19.